Clinical implications of four different nutritional indexes in patients with IgA nephropathy - Qian, Chuyue; Li, Huimin; Hou, Yue; Wang, Wanning; Sun, Mindan (Frontiers in Nutrition, 2024)
Background Immunoglobulin A nephropathy (IgAN) is the most prevalent form of chronic kidney disease (CKD), marked by diverse pathological patterns and variable prognostic outcomes. Nutritional indexes are crucial for disease assessment and prognosis prediction. This study investigates associations between nutritional indexes and renal function in patients with IgAN. Methods A cohort of 736 adults diagnosed with IgAN, who underwent renal biopsy at the First Hospital of Jilin University between January 2010 and October 2022, was examined. Clinical and laboratory data were reviewed, and four nutritional indexes were calculated: controlling nutritional status (CONUT) score, geriatric nutritional risk index (GNRI), body mass index (BMI), and prognostic nutritional index (PNI). Cox-proportional hazard analysis evaluated factors associated with end-stage renal disease (ESRD). Results Patients with ESRD showed significantly lower GNRI (91.84 vs. 98.94, p < 0.001) and median PNI (41.90 vs. 46.30, p < 0.001), with higher median CONUT score (2.00 vs. 1.00, p = 0.001) compared to those without ESRD. PNI, GNRI, and CONUT scores correlated significantly with C2 in MEST-C classification. Kaplan–Meier analysis indicated increased ESRD probability in individuals with specific thresholds of PNI, GNRI, or CONUT scores. Additionally, GNRI emerged as an independent predictor of ESRD (hazard ratio: 0.963, 95% CI: 0.940–0.979, p < 0.001), along with platelet count, serum creatinine, eGFR (CKD-EPI), and triglyceride levels. Conclusion GNRI, PNI, and CONUT scores hold potential in reflecting IgAN severity and predicting ESRD risk. GNRI especially may serve as a valuable tool for identifying high-risk individuals for ESRD in IgAN.